Shifting Winds: Mobility Trends Among Indian and Chinese Students - Mason, Leah; Martel, Mirka (International Higher Education, 2025)
<h3 id="this-article-examines-the-changing-enrollment-patterns-of-international-students-from-leading-senders-china-and-india-to-host-destinations-around-the-world-using-data-from-the-past-decade-we-offer-a-divergent-picture-of-the-priorities-of-these-students-and-the-implications-for-policies-and-academic-mobility" data-pm-slice="1 1 []">This article examines the changing enrollment patterns of international students from leading senders China and India to host destinations around the world. Using data from the past decade, we offer a divergent picture of the priorities of these students and the implications for policies and academic mobility.